Early ACEI/ARB use and in-hospital outcomes of acute myocardial infarction patients with systolic blood pressure <100 mmHg and undergoing percutaneous coronary intervention: Findings from the CCC-ACS project - Zhao, Xuedong; Zhao, Guanqi; Zhou, Mengge; Wang, Ge; Ma, Changsheng; Smith, Sidney C.; Fonarow, Gregg C.; Morgan, Louise; Que, Bin; Ai, Hui; Liu, Jing; Zhao, Dong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Few studies have especially evaluated whether acute myocardial infarction (AMI) patients with SBP<100 mmHg but without cardiogenic shock at admission derive benefits from early ACEI/ARB use in the era of percutaneous coronary intervention (PCI). Objectives: This study evaluated the associations of ACEI/ARB use within 24 hours of admission with in-hospital outcomes among AMI patients with SBP<100 mmHg and undergoing PCI. Methods: This study was based on the Improving Care for Cardiovascular Disease in China-ACS project, a collaborative registry and quality improvement project of the American Heart Association and the Chinese Society of Cardiology. Between November 2014 and December 2019, a total of 94623 patients with AMI were enrolled. Of them, 4478 AMI patients with SBP<100 mmHg and undergoing PCI but without clinically diagnosed cardiogenic shock at admission were included. Multivariable logistic regression and propensity score-matching analysis were used to evaluate the association between early ACEI/ARB use and in-hospital major adverse cardiac event (MACE), a combination of all-cause death, cardiogenic shock, and cardiac arrest. Results: Of AMI patients, 24.41% (n=1093) were prescribed ACEI/ARB within 24 hours of admission. Patients with ACEI/ARB use had a significantly lower rate of MACE compared with those without ACEI/ARB use (2.10% vs. 4.28%, p=0.001). In the logistic regression analysis, early ACEI/ARB use was associated with a 45% lower risk of MACE (odds ratio: 0.55, 95% CI: 0.33-0.93; p=0.027). Further propensity score-matching analysis still showed that patients with early ACEI/ARB use had a lower rate of MACE (2.11% vs. 3.67%, p=0.03). Conclusions: This study finds that among AMI patients with admission SBP < 100 mmHg undergoing PCI, early ACEI/ARB use is associated with better in-hospital outcomes. Additional studies of early use of ACEI/ARB in AMI patients with relatively low blood pressure are warranted.